Vanadium-doped Co9S8 nanosheet array as well as preparation method and application thereof

By doping vanadium elements in Co9S8 and using Co-ZIF precursors to prepare a vanadium-doped Co9S8 nanosheet array, the problem of specific capacity attenuation of a single Co9S8 electrode material is solved, and the improvement of high specific capacitance and good rate performance is achieved.

CN119581234APending Publication Date: 2025-03-07NINGBO UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411710019.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-27
Publication Date
2025-03-07

AI Technical Summary

Technical Problem

A single Co9S8 electrode material is prone to volume expansion during redox reactions, resulting in rapid attenuation of specific capacity, limiting its practical application.

Method used

By doping vanadium in Co9S8, using Co-ZIF as the precursor, combining foam nickel as the basic skeleton, and adjusting the vulcanization conditions, a vanadium-doped Co9S8 nanosheet array was prepared.

Benefits of technology

The bimetallic synergistic effect formed by vanadium doping improves electron transfer rate, enhances electrochemical activity and charge storage capabilities, and significantly improves the specific capacitance and rate performance of the material.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119581234A_ABST
    Figure CN119581234A_ABST
Patent Text Reader

Abstract

The invention provides a vanadium-doped Co9S8 nanosheet array as well as a preparation method and application thereof. The invention provides a vanadium-doped Co9S8 nanosheet array preparation method, which comprises: dissolving a cobalt salt and 2-methylimidazole in deionized water, adding foamed nickel, and carrying out a reaction at a room temperature to obtain a Co-ZIF nanosheet array precursor; then adding the VCo-ZIF nanosheets into a sodium metavanadate solution, and carrying out hydrothermal reaction to obtain a VCo-ZIF nanosheet array; and finally, adding the VCo-ZIF into a sulfur source solution, and vulcanizing to obtain the vanadium-doped Co9S8 nanosheet array. The formed porous nanosheet structure can provide a larger active specific surface area, the synergistic effect between Co and V ions can improve the charge storage capacity of the material, and sulfur vacancies on the surface of the electrode material can increase the conductivity and the number of active sites. Practice shows that when the material is used as a supercapacitor electrode material, the specific capacity and the rate capability are remarkably improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the cross-field of nano material preparation method and electrochemical application, and specifically relates to a vanadium-doped Co9S8 nanosheet array and a preparation method and application thereof. Background Art

[0002] As an innovative and environmentally friendly energy storage device, supercapacitors are a new type of device between traditional capacitors and rechargeable batteries. Its notable features include ultra-long service life, excellent power density, wide operating temperature adaptability, relatively low cost and environmentally friendly properties. These advantages make supercapacitors show broad application prospects in many fields such as portable electronic products and new energy vehicles. Among them, the performance of electrode materials plays a decisive role in the overall performance of supercapacitors. Therefore, electrode materials with high performance potential have become the key to improving the technical level of supercapacitors and an important reason for promoting their wide application in various fields.

[0003] Transition metal sulfides such as Co9S8 have the advantages of high theoretical specific capacitance, good conductivity, and rich reaction valence states, and are considered to be one of the most promising electrode materials. However, the specific capacity of single Co9S8 is still not ideal. It is easy to expand in volume during redox reactions, causing the specific capacity to decay rapidly, which greatly limits its practical application. Doping with heterometallic elements can improve the electronic structure of the material, increase the charge transfer efficiency, reduce the oxidation reaction energy barrier, and increase the capacity; at the same time, constructing a nanoarray can reduce agglomeration and improve the stability of the electrode material, which is an effective way to improve the performance of Co9S8 electrode materials. Summary of the invention

[0004] In order to solve the above technical problems, the present invention adopts a simple and low-cost preparation method to realize the preparation of a vanadium-doped Co9S8 nanosheet array. In this study, nickel foam is used as the basic skeleton, Co-ZIF is used as the precursor, and vanadium element is used as the doping ion. A vanadium-doped Co9S8 nanosheet array is prepared by adjusting the sulfurization conditions. Since Co-ZIF as a precursor has adjustable porosity and high specific surface area, it can provide abundant active sites; the bimetallic synergistic effect formed by vanadium ion doping accelerates the electron transfer rate and enhances the charge storage capacity. The advantages of this study are: (1) a porous metal sulfide array derived from Co-ZIF is prepared, which improves the porosity and electron transfer efficiency of the material. (2) The bimetallic synergistic effect formed by vanadium metal element doping can increase the electron transfer rate and enhance the electrochemical activity, and its rich oxidation valence state can enhance the charge storage capacity of the material.

[0005] The present invention provides a method for preparing a vanadium-doped Co9S8 nanosheet array, comprising the following steps:

[0006] (1) dissolving cobalt salt and 2-methylimidazole in 50 mL of deionized water to obtain a reaction solution, placing the cleaned nickel foam in the reaction solution, reacting at room temperature for a period of time, washing with distilled water, and drying in a forced air drying oven to obtain a Co-ZIF nanosheet array precursor;

[0007] (2) dissolving the vanadium source in 40 mL of deionized water, mixing and stirring for 30 minutes to obtain a uniform reaction solution, placing the Co-ZIF nanosheet array precursor prepared in step (1) into the reaction solution, transferring it to a 100 mL reactor, and performing a hydrothermal reaction to obtain a VCo-ZIF nanosheet array;

[0008] (3) Disperse the sulfur source in 50 ml of anhydrous ethanol and stir for 30 minutes. Put the VCo-ZIF nanosheet array prepared in step (2) into the reaction solution and transfer it to a 100 mL reactor for sulfurization reaction to obtain a vanadium-doped Co9S8 nanosheet array, referred to as V-Co9S8.

[0009] In step (1), the type of cobalt salt is not limited, including cobalt chloride, cobalt nitrate, cobalt acetate, etc., but cobalt nitrate hexahydrate is most preferred.

[0010] In the step (1), the molar ratio of cobalt nitrate hexahydrate to 2-methylimidazole is optimized to (1-3): (7-10), but the optimal ratio is 1:4.

[0011] In the step (2), the type of vanadium source is not limited, including one or more of ammonium metavanadate, sodium metavanadate, potassium metavanadate, and sodium orthovanadate, but sodium metavanadate is most preferred.

[0012] In the step (2), the amount of the vanadium source is preferably 0.05 to 0.5 g.

[0013] In the step (2), the hydrothermal reaction temperature is preferably 90 to 150° C., and the hydrothermal reaction time is preferably 0.5 to 5 hours.

[0014] In step (3), the type of sulfur source is not limited, including one or more of sodium sulfide, thiourea, and thioacetamide, but thioacetamide is most preferred.

[0015] In the step (3), the sulfurization reaction temperature is preferably 85 to 145° C., and the sulfurization reaction time is preferably 2 to 8 hours, but most preferably the reaction is performed at 125° C. for 5 hours.

[0016] In summary, the vanadium-doped Co9S8 nanosheet array of the present invention has the following beneficial effects:

[0017] (1) The cost of raw materials required to prepare V-Co9S8 is low, and the synthesis process is simple. It can be synthesized only by room temperature in-situ growth method and hydrothermal method. Using Co-ZIF as a template to prepare porous nanosheets can increase the active sites of redox reactions, shorten the path of ion diffusion, and inhibit the accumulation and agglomeration of nanosheets; the bimetallic synergistic effect formed by vanadium doping can increase the electron transfer rate and enhance the electrochemical activity, and its rich oxidation valence state can enhance the charge storage capacity of the material; vanadium doping produces a large number of sulfur vacancies on the surface of the electrode material, further improving the conductivity and the number of active sites, so that this material can be improved in many aspects such as specific capacitance and rate performance; directly constructing an array structure on a nickel foam substrate can improve the mechanical stability and conductivity of the dot material.

[0018] (2) The vanadium-doped Co9S8 nanosheet array prepared by the present invention exhibits high specific capacitance and rate performance in electrochemical tests. The cyclic voltammetry curve and the constant current charge-discharge curve were measured using a CHI 660E electrochemical workstation. The cyclic voltammetry curve test was carried out at a scan rate of 5, 10, 20, 30, 50 and 100 mV / s, and the voltage range was 0 to 0.7 V. The constant current charge-discharge test was carried out at current densities of 1, 2, 3, 5 and 10 A / g, and the voltage range was 0 to 0.45 V. At a current density of 1 A / g, the electrode material has a high specific capacitance of 1553 F / g, and even at a current density of 10 A / g, the electrode material has a specific capacitance of 675 F / g, and the rate performance is good.

[0019] (3) The preparation method of the present invention is simple and effective, and the construction of the vanadium-doped electrode material demonstrated can be simply extended to construct other defect-rich metal sulfide array electrode materials for energy storage devices. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] Figure 1 This is a scanning electron microscope image of the Co-ZIF nanosheet array precursor prepared in step (1) of Example 1 of the present invention;

[0021] Figure 2 This is a scanning electron microscope image of the VCo-ZIF nanosheet array prepared in step (2) of Example 1 of the present invention;

[0022] Figure 3 This is a scanning electron microscope image of the V-Co9S8 nanosheet array prepared in step (3) of Example 1 of the present invention;

[0023] Figure 4 The X-ray diffraction pattern of the V-Co9S8 nanosheet array prepared in step (3) of Example 1 of the present invention is compared with the standard card;

[0024] Figure 5The electron paramagnetic resonance curves of the V-Co9S8 nanosheet array prepared in step (3) of Example 1 of the present invention and the Co9S8 nanosheet array prepared in step (2) of the comparative example;

[0025] Figure 6 The electrochemical performance diagram of the V-Co9S8 nanosheet array prepared in step (3) of Example 1 of the present invention as an electrode material in a 2M KOH electrolyte solution, the left figure is a cyclic voltammetry curve at different scan rates, and the right figure is a charge-discharge curve at different current densities;

[0026] Figure 7 The specific capacitance of the V-Co9S8 nanosheet array prepared in step (3) of Example 1 of the present invention and the Co9S8 nanosheet array prepared in step (2) of the comparative example as electrode materials in 2M KOH electrolyte solution is compared. DETAILED DESCRIPTION

[0027] The preferred embodiments of the present invention are described in further detail below with reference to the accompanying drawings and examples.

[0028] Example 1

[0029] A method for preparing a vanadium-doped Co9S8 nanosheet array comprises the following steps:

[0030] (1) 0.36 g of cobalt nitrate hexahydrate and 0.82 g of 2-methylimidazole were dissolved in 50 mL of deionized water to obtain a reaction solution, and the cleaned nickel foam was placed in the reaction solution, reacted at room temperature for 2 h, washed with distilled water, and then dried in a blast drying oven to obtain a Co-ZIF nanosheet array precursor; its scanning electron microscopy was as follows Figure 1 As shown, it presents a triangular nanosheet morphology with a smooth surface and a certain thickness;

[0031] (2) 0.16 g of sodium metavanadate was dissolved in 40 mL of deionized water and stirred for 30 minutes to obtain a uniform reaction solution. The Co-ZIF nanosheet array precursor prepared in step (1) was placed in the reaction solution and transferred to a 100 mL reactor for hydrothermal reaction at 120° C. for 2 hours to obtain a VCo-ZIF nanosheet array. The scanning electron microscope image is shown in FIG. Figure 2 As shown, it presents a rough surface and porous triangular nanosheet morphology;

[0032] (3) Disperse 1.5 g of thioacetamide in 50 ml of anhydrous ethanol and stir for 30 minutes. Place the VCo-ZIF nanosheet array prepared in step (2) into the reaction solution and transfer it to a 100 mL reactor. Perform a sulfurization reaction at 125° C. for 5 hours to obtain a vanadium-doped Co9S8 nanosheet array, referred to as V-Co9S8. The scanning electron microscope image is shown in FIG. Figure 3As shown, it presents a rough nanosheet morphology, which are interconnected to form a network structure.

[0033] The X-ray diffraction pattern of V-Co9S8 prepared in the above steps is as follows Figure 4 As shown, the diffraction peaks are all attributed to Co9S8 (JCPDS No.65-1765).

[0034] The V-Co9S8 prepared above and the Co9S8 in the comparative example were tested for electron paramagnetic resonance curves. Figure 5 As shown, V-Co9S8 has a stronger signal, indicating that there are a large number of sulfur vacancies on the surface of V-Co9S8, which is beneficial to adjust the electronic structure and improve the electrochemical performance.

[0035] The V-Co9S8 prepared above was used as a supercapacitor electrode material, and its electrochemical performance was tested in a 2M KOH electrolyte solution. Figure 6 The left figure is the cyclic voltammetry curve at different scan rates, and the right figure is the charge and discharge curve at different current densities.

[0036] The V-Co9S8 prepared above was used as a supercapacitor electrode material, and its specific capacitance at different current densities was tested in a 2M KOH electrolyte solution. Figure 7 As shown, V-Co9S8 has a high specific capacitance of 1553F / g at 1A / g, while the Co9S8 prepared in the comparative example has a specific capacitance of only 1011F / g, indicating that the electrochemical performance is greatly improved by vanadium doping and the introduction of sulfur vacancies.

[0037] Example 2

[0038] (1) Dissolving 0.72 g of cobalt nitrate hexahydrate and 0.82 g of 2-methylimidazole in 50 mL of deionized water to obtain a reaction solution, placing the cleaned nickel foam into the reaction solution, reacting at room temperature for 2 h, washing with distilled water, and drying in a forced air drying oven to obtain a Co-ZIF nanosheet array precursor;

[0039] (2) dissolving 0.16 g of sodium metavanadate in 40 mL of deionized water and stirring for 30 minutes to obtain a uniform reaction solution, placing the Co-ZIF nanosheet array precursor prepared in step (1) into the reaction solution, transferring the solution to a 100 mL reactor, and subjecting the reaction to a hydrothermal reaction at 120° C. for 2 hours to obtain a VCo-ZIF nanosheet array;

[0040] (3) Disperse 1.5 g of thioacetamide in 50 ml of anhydrous ethanol and stir for 30 minutes. Place the VCo-ZIF nanosheet array prepared in step (2) into the reaction solution, transfer it to a 100 mL reactor, and perform a sulfurization reaction at 125° C. for 5 hours to obtain a vanadium-doped Co9S8 nanosheet array, referred to as V-Co9S8.

[0041] The prepared V-Co9S8 nanosheet array was used as a supercapacitor electrode material, and its specific capacitance at different current densities was tested in a 2M KOH electrolyte solution. The electrode material had a specific capacitance of 1436.2 F / g at 1 A / g.

[0042] Example 3

[0043] (1) 0.36 g of cobalt nitrate hexahydrate and 0.82 g of 2-methylimidazole were dissolved in 50 mL of deionized water to obtain a reaction solution, the cleaned nickel foam was placed in the reaction solution, reacted at room temperature for 2 h, washed with distilled water, and then dried in a forced air drying oven to obtain a Co-ZIF nanosheet array precursor;

[0044] (2) dissolving 0.16 g of sodium metavanadate in 40 mL of deionized water and stirring for 30 minutes to obtain a uniform reaction solution, placing the Co-ZIF nanosheet array precursor prepared in step (1) into the reaction solution, transferring the mixture to a 100 mL reactor, and subjecting the mixture to a hydrothermal reaction at 100° C. for 2 hours to obtain a VCo-ZIF nanosheet array;

[0045] (3) Disperse 1.5 g of thioacetamide in 50 ml of anhydrous ethanol and stir for 30 minutes. Place the VCo-ZIF nanosheet array prepared in step (2) into the reaction solution, transfer it to a 100 mL reactor, and perform a sulfurization reaction at 125° C. for 5 hours to obtain a vanadium-doped Co9S8 nanosheet array, referred to as V-Co9S8.

[0046] The prepared V-Co9S8 nanosheet array was used as a supercapacitor electrode material, and its specific capacitance at different current densities was tested in a 2M KOH electrolyte solution. The electrode material had a specific capacitance of 1398.3 F / g at 1 A / g.

[0047] Example 4

[0048] (1) Dissolve 0.36 g of cobalt nitrate hexahydrate and 0.82 g of 2-methylimidazole in 50 mL of deionized water to obtain a reaction solution, put the cleaned nickel foam into the reaction solution, react at room temperature for 2 h, wash with distilled water, and then dry in a forced air drying oven to obtain a Co-ZIF nanosheet array precursor;

[0049] (2) dissolving 0.32 g of sodium metavanadate in 40 mL of deionized water and stirring for 30 minutes to obtain a uniform reaction solution, placing the Co-ZIF nanosheet array precursor prepared in step (1) into the reaction solution, transferring the solution to a 100 mL reactor, and subjecting the reaction to a hydrothermal reaction at 120° C. for 2 hours to obtain a VCo-ZIF nanosheet array;

[0050] (3) Disperse 1.5 g of thioacetamide in 50 ml of anhydrous ethanol and stir for 30 minutes. Place the VCo-ZIF nanosheet array prepared in step (2) into the reaction solution, transfer it to a 100 mL reactor, and perform a sulfurization reaction at 125° C. for 5 hours to obtain a vanadium-doped Co9S8 nanosheet array, referred to as V-Co9S8.

[0051] The prepared V-Co9S8 nanosheet array was used as a supercapacitor electrode material, and its specific capacitance at different current densities was tested in a 2M KOH electrolyte solution. The electrode material had a specific capacitance of 1403.3 F / g at 1 A / g.

[0052] Example 5

[0053] (1) 0.36 g of cobalt nitrate hexahydrate and 0.82 g of 2-methylimidazole were dissolved in 50 mL of deionized water to obtain a reaction solution, and the cleaned nickel foam was placed in the reaction solution, reacted at room temperature for 2 h, washed with distilled water, and then dried in a blast drying oven to obtain a Co-ZIF nanosheet array precursor; its scanning electron microscopy was as follows Figure 1 As shown, it presents a triangular nanosheet morphology with a smooth surface and a certain thickness;

[0054] (2) dissolving 0.16 g of sodium metavanadate in 40 mL of deionized water and stirring for 30 minutes to obtain a uniform reaction solution, placing the Co-ZIF nanosheet array precursor prepared in step (1) into the reaction solution, transferring the solution to a 100 mL reactor, and subjecting the reaction to a hydrothermal reaction at 120° C. for 2 hours to obtain a VCo-ZIF nanosheet array;

[0055] (3) Disperse 1.5 g of thioacetamide in 50 ml of anhydrous ethanol and stir for 30 minutes. Put the VCo-ZIF nanosheet array prepared in step (2) into the reaction solution, transfer it to a 100 mL reactor, and perform a sulfurization reaction at 105° C. for 5 hours to obtain a vanadium-doped Co9S8 nanosheet array, referred to as V-Co9S8.

[0056] The prepared V-Co9S8 nanosheet array was used as a supercapacitor electrode material, and its specific capacitance at different current densities was tested in a 2M KOH electrolyte solution. The electrode material had a specific capacitance of 1339 F / g at 1 A / g.

[0057] Comparative Example

[0058] A method for preparing a Co9S8 nanosheet array comprises the following steps:

[0059] (1) 0.36 g of cobalt nitrate hexahydrate and 0.82 g of 2-methylimidazole were dissolved in 50 mL of deionized water to obtain a reaction solution, the cleaned nickel foam was placed in the reaction solution, reacted at room temperature for 2 h, washed with distilled water, and then dried in a forced air drying oven to obtain a Co-ZIF nanosheet array precursor;

[0060] (2) Disperse 1.5 g of thioacetamide in 50 ml of anhydrous ethanol and stir for 30 minutes. Put the Co-ZIF nanosheet array precursor prepared in step (1) into the reaction solution, transfer it to a 100 mL reactor, and perform a sulfurization reaction at 125° C. for 5 hours to obtain a Co9S8 nanosheet array.

[0061] The Co9S8 prepared above was subjected to an electron paramagnetic resonance curve test. Figure 5 shown.

[0062] The Co9S8 nanosheet arrays prepared above were used as supercapacitor electrode materials, and their specific capacitance at different current densities was tested in a 2M KOH electrolyte solution. Figure 7 As shown, Co9S8 has a specific capacitance of 1011F / g at 1A / g.

[0063] The embodiments described above are detailed descriptions of the technical solutions of the present invention, which should be understood as specific implementation measures of the present invention and are not used to summarize the present invention. Any modifications, supplements or similar replacements made within the scope of the principles of the present invention shall fall within the scope of protection that the present invention should enjoy.

Claims

1. A method for preparing a vanadium-doped Co9S8 nanosheet array, characterized in that: The preparation method comprises the following steps: (1) 0.36 g of cobalt nitrate hexahydrate and 0.82 g of 2-methylimidazole were dissolved in 50 mL of deionized water to obtain a reaction solution, the cleaned nickel foam was placed in the reaction solution, reacted at room temperature for 2 h, washed with distilled water, and then dried in a forced air drying oven to obtain a Co-ZIF nanosheet array precursor; (2) dissolving 0.16 g of sodium metavanadate in 40 mL of deionized water and stirring for 30 minutes to obtain a uniform reaction solution, placing the Co-ZIF nanosheet array precursor prepared in step (1) into the reaction solution, transferring the solution to a 100 mL reactor, and subjecting the reaction to a hydrothermal reaction at 120° C. for 2 hours to obtain a VCo-ZIF nanosheet array; (3) Disperse 1.5 g of thioacetamide in 50 ml of anhydrous ethanol and stir for 30 minutes. Add the VCo-ZIF nanosheet array prepared in step (2) to the reaction solution, transfer it to a 100 mL reactor, and perform a sulfurization reaction at 125° C. for 5 hours to obtain a vanadium-doped Co9S8 nanosheet array.

2. The vanadium-doped Co9S8 nanosheet array prepared by the preparation method according to claim 1, characterized in that: The vanadium-doped Co9S8 nanosheets grow on a nickel foam support and are interconnected to form a network structure.

3. The vanadium-doped Co9S8 nanosheet array according to claim 2, characterized in that: The surface of the vanadium-doped Co9S8 nanosheets contains a large number of sulfur vacancies.

4. Use of the vanadium-doped Co9S8 nanosheet array prepared by the preparation method according to claim 1 as a supercapacitor electrode material.